2018
DOI: 10.1021/acs.est.7b04570
|View full text |Cite
|
Sign up to set email alerts
|

Application of Proton-Transfer-Reaction Mass Spectrometry (PTR-MS) and 33S Isotope Labeling for Monitoring Sulfur Processes in Livestock Waste

Abstract: Reduced sulfur compounds emitted from livestock production cause odor nuisance for local residents. The microbial processes responsible for this are not well described in swine manure and a method for monitoring the biological processes is necessary to develop strategic abatement technologies. In this study, Proton-Transfer-Reaction Mass Spectrometry and isotope-labeled sulfate were combined and applied to elucidate the sulfur processes in swine manure with high time resolution. We successfully monitored reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…The isotope ratio in unlabeled control manure was in close agreement with the theoretical isotope ratio based on a reference R ( 33/32 S) of 0.788% [ 33 ]. The labeled controls indicate that approximately 80% of the hydrogen sulfide was produced by reduction of sulfate ( Fig 5A ), which is consistent with previous estimates of 77 ± 3% in swine manure [ 7 ]. Treatment with TA-NaF yielded a R ex ( 33/32 S) H2S value similar to the R ex ( 33/32 S) SO4 value, suggesting that more than 95% of the emitted hydrogen sulfide was derived from sulfate reduction.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The isotope ratio in unlabeled control manure was in close agreement with the theoretical isotope ratio based on a reference R ( 33/32 S) of 0.788% [ 33 ]. The labeled controls indicate that approximately 80% of the hydrogen sulfide was produced by reduction of sulfate ( Fig 5A ), which is consistent with previous estimates of 77 ± 3% in swine manure [ 7 ]. Treatment with TA-NaF yielded a R ex ( 33/32 S) H2S value similar to the R ex ( 33/32 S) SO4 value, suggesting that more than 95% of the emitted hydrogen sulfide was derived from sulfate reduction.…”
Section: Resultssupporting
confidence: 91%
“…Though cysteine degradation was almost completely inhibited, it remains unclear exactly how methionine degradation was affected. It has been shown that methanethiol from swine manure originates primarily from methionine degradation [ 7 ], and hence a huge reduction in methanethiol production, as those seen for TA-NaF treatment in this study, is likely to result from inhibition of methionine degradation. The limited production of methanethiol made it challenging to achieve the precision needed to differentiate between the untreated control manure and TA-NaF treated manure.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Common practice is to lower the pH to 5.5 with H 2 SO 4 with reported CH 4 reductions of 63–99% [ 6 ]. Proposed inhibition mechanisms include H 2 S-mediated inhibition [ 7 ], which is mainly derived from sulfate reduction [ 8 ], uncoupling of the cell membrane by protonated fermentative products [ 9 , 10 ], or competitive inhibition of methanogens by microorganisms able to respire more energetic electron acceptors [ 11 ]. The latter may be relevant if acidification is carried out using H 2 SO 4 or HNO 3 , which dissociates to the more preferable electron acceptors, sulfate and nitrate, than CO 2 during methanogenesis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] Measuring 13 C/ 12 C ratios in CH 4 and CO 2 emitted from manure using CRDS may enhance our understanding of the methanogenic pathways contributing to CH 4 emissions from livestock facilities. 5,23 However, NH 3 and livestock trace gases such as H 2 S are often present at ppm levels [24][25][26] and may exceed the CH 4 concentrations inside buildings where animals are kept. NH 3 cross-interference on 13 C/ 12 C ratios in CH 4 was reported recently, 18 and H 2 S crossinterference on 13 C/ 12 C ratios in CO 2 was thoroughly described by Malowany et al 27 These interferences may disturb 13 C/ 12 C measurements to the detriment of evaluating the relative contribution of methanogenic pathways.…”
mentioning
confidence: 99%